1989
DOI: 10.1302/0301-620x.71b5.2584249
|View full text |Cite
|
Sign up to set email alerts
|

The total condylar prosthesis. 10- to 12-year results of a cemented knee replacement

Abstract: good. There were three (4.0%) fair and six (8.2%) poor results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(53 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…The majority of patients undergoing TKA have excellent clinical results [14,18,19,21]. A minority of patients may experience knee pain, stiffness, and/or patellar instability One or more of the authors (CH, KLG) have received funding that is not related to the content of this manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients undergoing TKA have excellent clinical results [14,18,19,21]. A minority of patients may experience knee pain, stiffness, and/or patellar instability One or more of the authors (CH, KLG) have received funding that is not related to the content of this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that rotational malalignment of the femoral and/or tibial components causes these problems, and because of this belief, malrotation is a major cause of revision TKA [4,21]. Others have written that rotational component alignment can cause rotational knee instability and even posterior dislocations of the knee after TKA [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although most patients experience relief of pain and improved function and quality of life [15,26,39,54], various suboptimal outcomes do occur, ranging from mild anterior knee pain to failures requiring revision surgery [5,38]. Patients with these suboptimal outcomes often report excessive joint stiffness or looseness [8,43], limited ROM [41], and difficulty with activities of daily living, such as climbing stairs and walking [10].…”
Section: Introductionmentioning
confidence: 99%
“…The TC knee would prove to have a high percentage of success, widely used, and would later demonstrates long survival [13].…”
Section: Functional Approachmentioning
confidence: 99%